EMINENT ASTRONOMERS - GRADUATES OF THE ODESSA UNIVERSITY - Volyanskaya, M. Yu. (Одеські астрономічні публікації, 2017)
The brief description of scientific activity represented of the eminent Astronomers - graduates of the Odessa University named after I.I.Mechnikov (earlier named as Novorossiyski university).